2003
DOI: 10.1002/pros.10200
|View full text |Cite
|
Sign up to set email alerts
|

Neuregulin promotes autophagic cell death of prostate cancer cells

Abstract: These results suggest that NRG induces type II cell death of LNCaP cells through PI3K-dependent pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 39 publications
1
21
1
Order By: Relevance
“…However, in prostate cancer, there are conflicting reports as to whether the ErbB4 protein is expressed (43) or not (10) in primary cancers. It has been suggested that NRG1 is able to inhibit prostate cell growth and division (10), induce apoptosis (44) and promote differentiation (45). At this time, it is therefore difficult to suggest hypotheses regarding the role of the NRGs in this disease, but a minimal requirement is to know the components of the system so that experiments that are able to explore this system can be designed.…”
Section: Discussionmentioning
confidence: 99%
“…However, in prostate cancer, there are conflicting reports as to whether the ErbB4 protein is expressed (43) or not (10) in primary cancers. It has been suggested that NRG1 is able to inhibit prostate cell growth and division (10), induce apoptosis (44) and promote differentiation (45). At this time, it is therefore difficult to suggest hypotheses regarding the role of the NRGs in this disease, but a minimal requirement is to know the components of the system so that experiments that are able to explore this system can be designed.…”
Section: Discussionmentioning
confidence: 99%
“…For example, activating mutations of ras proto-oncogenes, the most frequently mutated protooncogenes in human tumors, trigger autophagy in glioblastoma as well as colon and gastric cancer cells (Chi et al, 1999;Pattingre et al, 2003). The ability of Ras to cause autophagy may explain the autophagy observed in prostate cancer cells following activation of ErbB2 and ErbB3 (receptor tyroisine kinases that activate Ras pathway) (Tal-Or et al, 2003). Interestingly, one of the signalling pathways regulated by Ras, the Raf-Erk1/2 pathway, triggers autophagy (Pattingre et al, 2003), whereas another downstream arm of Ras signalling, PI3K-PKB pathway, inhibits it (Arico et al, 2001).…”
Section: Promotion and Inhibition Of Pcd During Tumourigenesismentioning
confidence: 99%
“…EGFR, HER3, and HER4 are activated via ligand binding, which results in the formation of homodimers or heterodimers with other family members (4). As HER2 ligands have not been identified, HER2 is believed to be activated by forming heterodimers with other family members (3,5). Formation of HER receptor homodimers or heterodimers results in receptor activation via tyrosine kinase -mediated autophosphorylation, resulting in phosphorylation and activation of downstream pathways, such as the mitogen-activated protein kinase cascade and the phosphatidylinositol 3-kinase (PI3K)/Akt cascade (6).…”
mentioning
confidence: 99%